Gender-specific aspects of epidemiology, molecular genetics and outcome: lung cancer. (3rd November 2020) - Mederos, Nuria; Friedlaender, Alex; Peters, Solange; Addeo, Alfredo
Abstract : Lung cancer remains the leading cause of cancer-related deaths worldwide in women and men. In incidence, lung cancer ranks second, surpassed by breast cancer in women and prostate cancer in men. However, the historical differences in mortality and incidence rate between both sexes have changed in the last years. In the last decades, we have also witnessed an increased number of lung cancer in female never-smokers. These disparities have grown our interest in studying the impact of the gender and sex in the presentation of lung cancer. The aetiology is yet to be fully elucidated, but the data are clear so far: there is a growing divide between lung cancer presentation in women and men that will change our management and study of lung cancer. This article aims to review the sex and gender differences in lung cancer.